2012
DOI: 10.1371/journal.pone.0037802
|View full text |Cite
|
Sign up to set email alerts
|

ILK Induces Cardiomyogenesis in the Human Heart

Abstract: BackgroundIntegrin-linked kinase (ILK) is a widely conserved serine/threonine kinase that regulates diverse signal transduction pathways implicated in cardiac hypertrophy and contractility. In this study we explored whether experimental overexpression of ILK would up-regulate morphogenesis in the human fetal heart.Methodology/Principal FindingsPrimary cultures of human fetal myocardial cells (19–22 weeks gestation) yielded scattered aggregates of cardioblasts positive for the early cardiac lineage marker nk×2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…Also, in the hearts of growth restricted E12.5 mouse fetuses (induced by 6 h of 8% oxygen prior to E12.5) VEGFa mRNA was increased 1.9 fold, but no changes were reported in other growth factors measured such as FGF-2 mRNA [44]. Although the expression of the genes selected in this study were not changed during DEX exposure, it is likely that other relevant genes may have been affected such as the recently identified novel cardiotropic factor integrin-linked kinase [45].…”
Section: Discussionmentioning
confidence: 63%
“…Also, in the hearts of growth restricted E12.5 mouse fetuses (induced by 6 h of 8% oxygen prior to E12.5) VEGFa mRNA was increased 1.9 fold, but no changes were reported in other growth factors measured such as FGF-2 mRNA [44]. Although the expression of the genes selected in this study were not changed during DEX exposure, it is likely that other relevant genes may have been affected such as the recently identified novel cardiotropic factor integrin-linked kinase [45].…”
Section: Discussionmentioning
confidence: 63%
“…Recently published studies revealed the importance of the cardiac lymphatic vasculature and its remodelling during the recovery phase after myocardial infarction (MI) (Ishikawa et al, 2007;Klotz et al, 2015;Henri et al, 2016;Tatin et al, 2017). Notably, the importance of ILK in cardiomyocytes and in regulating cardiac function was previously reported by several publications (Bendig et al, 2006;Lu et al, 2006;White et al, 2006;Ding et al, 2009;Gu et al, 2012;Traister et al, 2012). ILK protein is expressed in LECs sorted from the adult mouse heart (Appendix Fig S6D); however, to our knowledge, the function of ILK in cardiac lymphatic vessels has not yet been analysed.…”
Section: Ilk Regulates Lymphatic Vascular Growth After Myocardial Infmentioning
confidence: 97%
“…Integrin‐linked kinase (ILK), now known as a mechanoreceptor protein and the physical linker for integrins with the actin cytoskeleton, regulates a variety of signal transduction pathways associated with both cardiac hypertrophy and contractility/force transduction (Lu et al, 2006; Traister et al, 2012, 2014). It forms the IPAP1 complex with PINCH1 and α‐parvin proteins, which are linked to cell adhesion, motility, and fibroblast and epithelial cell survival (Chen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%